In-situ tumor vaccination by percutaneous ablative therapy and its synergy with immunotherapeutics: An update on combination therapy - Kim, Nicole J.; Yoon, Jessica H.; Tuomi, Adam C.; Lee, John; Kim, Daehee (Frontiers in Immunology, 2023)
Percutaneous tumor ablation is now a widely accepted minimally invasive local treatment option offered by interventional radiology and applied to various organs and tumor histology types. It utilizes extreme temperatures to achieve irreversible cellular injury, where ablated tumor interacts with surrounding tissue and host via tissue remodeling and inflammation, clinically manifesting as post-ablation syndrome. During this process, in-situ tumor vaccination occurs, in which tumor neoantigens are released from ablated tissue and can prime one’s immune system which would favorably affect both local and remote site disease control. Although successful in priming the immune system, this rarely turns into clinical benefits for local and systemic tumor control due to intrinsic negative immune modulation of the tumor microenvironment. A combination of ablation and immunotherapy has been employed to overcome these and has shown promising preliminary results of synergistic effect without significantly increased risk profiles. The aim of this article is to review the evidence on post-ablation immune response and its synergy with systemic immunotherapies.